Syi’ah: Pemikiran Keagamaan dan Perkembangannya di Indonesia - Farida, Umma (FIKRAH, 2017)
This article attempts to explore the Syi’ah religious thought by emphasizing on three areas, namely the field of theological belief (aqidah), methods and style of interpretation of the Quran (tafseer), and their attitude towards hadith. In addition, this paper discusses the development of Shi'ism in Indonesia. Method of data collection was done through the documentation which was then presented in descriptive-qualitative. Syi’ah is different from Suni (majority in Indonesia) in terms of the pillars of faith and the pillars of Islam. Their related Aqeedah, imamah, bada', raj'ah, and taqiyah implies on their way of understanding and interpreting the verses of the Quran. Their attitudes toward authenticity and sadnessahihan hadith also favor the transmission of ahlulbait rather than the transmission of the companions in general. Nevertheless, it turns out that Syi’ah ideology in Indonesia is still growing. The development of ideology is well-organized, supported by vision, mission, and moral foundation of humane da'wah through the empowerment of the weak and the underprivileged.